2012
DOI: 10.1007/978-3-642-30961-8_15
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis Techniques for Task-Based OpenMP Applications

Abstract: Abstract.Version 3.0 of the OpenMP specification introduced the task construct for the explicit expression of dynamic task parallelism. Although automated load-balancing capabilities make it an attractive parallelization approach for programmers, the difficulty of integrating this new dimension of parallelism into traditional models of performance data has so far prevented the emergence of appropriate performance tools. Based on our earlier work, where we have introduced instrumentation for task-based programs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Schmidl et al [16] described possible performance problems with OpenMP tasks and visualized trace data of tasks with Vampir [7]. However, manually searching a time-line visualization for certain performance patterns is tedious and time consuming.…”
Section: Related Workmentioning
confidence: 98%
See 1 more Smart Citation
“…Schmidl et al [16] described possible performance problems with OpenMP tasks and visualized trace data of tasks with Vampir [7]. However, manually searching a time-line visualization for certain performance patterns is tedious and time consuming.…”
Section: Related Workmentioning
confidence: 98%
“…This comes at the cost of additional task management overhead. Schmidl et al [16] identified three performance issues specifically related to OpenMP tasks:…”
Section: Problem Analysismentioning
confidence: 99%
“…In our fourth use case, we want to evaluate a task-based parallelization problem. One of the most common performance analysis targets is to identify tasks with inappropriate granularity [17]. For this purpose, we use an artificial program that has two task constructs.…”
Section: Task Granularitymentioning
confidence: 99%
“…Olivier et al [15] compared their scheduler in Qthreads with Intel's and GCC's OpenMP implementations concerning multi-socket SMPs. Schmidl et al [18] proposed a task-event model that helps profile performance on task-centric applications. Addison et al [16] created the OpenMP implementation in the compiler Open64 [17].…”
Section: Related Workmentioning
confidence: 99%